2-a-(-b)+c+(-a)-b-(-c)=0

Simple and best practice solution for 2-a-(-b)+c+(-a)-b-(-c)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-a-(-b)+c+(-a)-b-(-c)=0 equation:


Simplifying
2 + -1a + -1(-1b) + c + (-1a) + -1b + -1(-1c) = 0

Remove parenthesis around (-1b)
2 + -1a + -1 * -1b + c + (-1a) + -1b + -1(-1c) = 0

Multiply -1 * -1
2 + -1a + 1b + c + (-1a) + -1b + -1(-1c) = 0

Remove parenthesis around (-1c)
2 + -1a + 1b + c + (-1a) + -1b + -1 * -1c = 0

Multiply -1 * -1
2 + -1a + 1b + c + (-1a) + -1b + 1c = 0

Reorder the terms:
2 + -1a + (-1a) + 1b + -1b + c + 1c = 0

Combine like terms: -1a + (-1a) = -2a
2 + -2a + 1b + -1b + c + 1c = 0

Combine like terms: 1b + -1b = 0
2 + -2a + 0 + c + 1c = 0
2 + -2a + c + 1c = 0

Combine like terms: c + 1c = 2c
2 + -2a + 2c = 0

Solving
2 + -2a + 2c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2a + -2 + 2c = 0 + -2

Reorder the terms:
2 + -2 + -2a + 2c = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -2a + 2c = 0 + -2
-2a + 2c = 0 + -2

Combine like terms: 0 + -2 = -2
-2a + 2c = -2

Add '-2c' to each side of the equation.
-2a + 2c + -2c = -2 + -2c

Combine like terms: 2c + -2c = 0
-2a + 0 = -2 + -2c
-2a = -2 + -2c

Divide each side by '-2'.
a = 1 + c

Simplifying
a = 1 + c

See similar equations:

| 12*11-(15-9)/3-(9-6) | | 4x-3y=32 | | b+3/2b+(b+45)+(2b-90)+90=560 | | 3(x+4)-4=8 | | 4a+2=36-5 | | 12X11(15-9)/3-(9-6) | | -3.6-r=-(-6r+0.6) | | 8x^2-2xy+7y^2=8 | | 9(84)=9 | | -3c+7a+5+17b+2c+2c+b+(-7a)=0 | | 4(2x-7)+33=-5(x-5)+17x-28 | | -5(-2x+2)=-9x | | -7x-3y=-7 | | 6st+9t+10s-15= | | -32-7x=4(4x-8) | | -3.6-r=(-6r+0.6) | | 4+4x-x^2-x^3=0 | | 3x-15+x=180 | | -6-2(-9x-8)=-3 | | s=q+3/x | | .40c+4-.20c=-9 | | -23=-t | | b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 | | -8x-9+5x=-9x+3 | | x+3=5x+2 | | 4.9t^2+2.14t+42=0 | | 5F-9C=120 | | 3/2*16*1/2 | | 7/2*16*-1/2 | | .5x-2.3=0.7 | | 3x+7x+4=2x-6 |

Equations solver categories